The light and shades of the Synod of Bishops on the new evangelisation and for the transmission of the Christian faith - Valado Domínguez, Óscar (Razón y fe, 2018)
The remote and proximate preparation of a Synod has its difficulties but so does its celebration. This article provides the evidence of the difficulties of the last Synod. Finally, thanks to the intervention of a roman young, the synod fathers, most of them priest and bishops, were able to interpret their pastoral works in light of the saving mission of Christ.
Keywords: Lineamenta; Instrumentum laboris; Relatio ante diceptationem; propositions; Benedict XVI; freedom y creativity